Improving Revealed Preference Bounds on Demand Responses. - Blundell, R; Browning, M; Crawford, I (Wiley, 2007)
There are three key dimensions by which revealed preference bounds on consumer demand responses can be improved. The first relates to the improvements that arise from using expansion paths for given relative prices, E-bounds. The second concerns the addition of new price information. Thirdly, there are improvements due to assuming separability. Our previous research has examined the first two cases. In this article, we show how to impose separability assumptions within a fully nonparametric analysis and distinguish between weak and homothetic separability. We also apply these ideas to the analysis of demand responses using United Kingdom household level data.